LANDASAN FILOSOFIS PEMIKIRAN TASAWUF ABDURRAUF SINGKEL TENTANG ALLAH, MANUSIA, DAN ALAM - Ahmad Rivauzi (Jurnal Theologia, 2017)
Abstract: Abdurrauf Singkel (d. 1105 H / 1693 AD), was one of the great scholars of the 17th century and he was a key figure in the development of Islam, especially in the field of Sufism,it was as one of the forms of education in the aspect of mankind in the archipelago. Almost all of the Shaṭāriyyah lineage is centered on itself and through some of his students, this congregation is spread to various regions of the Malay-Nusantara world. Through the research with a hermeneutic approach to his works, this paper aims to reveal the philosophical foundation of the Abdurrauf Singkel thought about Sufism that puts the Quran and Ḥadith as the basis and normative source of it. The affirmation and reinforcement of tauhid, its reinterpretation to the concept of waḥdāt al-wujūd which places man as the shadow of Allah, the concept of the creation of nature through the process of emanation and awakening the consciousness of servanthood through the effort of dying (ikhtiyari) by fana in zikrullah as the way of recognizing the nature of being and ma'rifatullāh, is the philosophical foundation of the Sufism thought which he developed in the Shaṭāriyyah.Abstrak: Abdurrauf Singkel (w. 1105 H/1693 M), adalah salah seorang ulama besar pada abad ke-17 dan merupakan tokoh kunci dalam perkembangan Islam terutama pada bidang tasawuf sebagai salah satu bentuk pendidikan pada aspek keruhanian di Nusantara. Hampir semua silsilah tarekat Shaṭāriyyah berpusat kepada dirinya dan melalui sejumlah muridnya, tarekat ini tersebar ke berbagai wilayah di dunia Melayu-Nusantara. Melalui penelitan dengan pendekatan hermeneutik terhadap karya-karyanya, tulisan ini bertujuan untuk mengungkapkan landasan filosofis pemikiran tasawuf Abdurrauf  Singkel yang menempatkan al-Qur’an dan Hadis sebagai dasar dan sumber normatif dari pemikiran tasawufnya. Penelitian menemukan bahwa penegasan dan penguatan tauhid, reinterpretasinya terhadap konsep waḥdāt al-wujūd yang menempatkan manusia sebagai bayangan dari Allah, konsep penciptaan alam melalui proses pemancaran (emanasi) serta membangun kesadaran kehambaan melalui upaya mati ikhtiyari dengan cara fana dalam dzikrullah sebagai  jalan untuk mengenali hakikat wujud dan ma’rifatullāh, merupakan pondasi filosofis dari bangunan pemikiran tasawuf yang dikembangkannya dalam tarekat Shaṭāriyyah.